2022
DOI: 10.1371/journal.pmed.1003976
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of physical health multimorbidity in people with severe mental illness: An accumulated prevalence analysis of United Kingdom primary care data

Abstract: Background People with severe mental illness (SMI) have higher rates of a range of physical health conditions, yet little is known regarding the clustering of physical health conditions in this population. We aimed to investigate the prevalence and clustering of chronic physical health conditions in people with SMI, compared to people without SMI. Methods and findings We performed a cohort-nested accumulated prevalence study, using primary care data from the Clinical Practice Research Datalink (CPRD), which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…In fact, it has been reported in another study of 74220 hospitalized patients in Spain that such characteristics cluster in a community of chronic comorbidities [ 47 ]. Another investigation that included adults with mental disorders (e.g., depression) reported a comorbidity group with a higher prevalence of heart disease, respiratory disease, arthritis, kidney disease, and hypertension [ 23 ]. The present study reports that these chronic conditions present cross-network loadings on all three factors and are associated to a greater degree, indicating certain comorbidity pathways in the systemic representation of multimorbidity in American adults with depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been reported in another study of 74220 hospitalized patients in Spain that such characteristics cluster in a community of chronic comorbidities [ 47 ]. Another investigation that included adults with mental disorders (e.g., depression) reported a comorbidity group with a higher prevalence of heart disease, respiratory disease, arthritis, kidney disease, and hypertension [ 23 ]. The present study reports that these chronic conditions present cross-network loadings on all three factors and are associated to a greater degree, indicating certain comorbidity pathways in the systemic representation of multimorbidity in American adults with depression.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, other possible biomarkers including anemia, C-reactive protein, and cystatin C have been identified [85]. Other studies that have reported similar comorbidity patterns have evidenced a high burden of mental illness [23]. In particular, previous studies have found strong correlations between cardiovascular disease and depression [86].…”
Section: Cardiovascular Diseases (Heart Attack-coronary Heartmentioning
confidence: 93%
See 1 more Smart Citation
“…While diabetes, hypertension, and respiratory diseases presented cross-network loadings with the third latent factor [cardiovascular (CVD) and renal diseases]. Another investigation that considered older adults with neurological problems in the United Kingdom reported a cardiovascular comorbidity group with a higher prevalence that included such conditions ( 23 ). In addition, another investigation conducted in the Chinese population using the factor analysis method to group comorbidity patterns reported that diabetes and hypertension share a common underlying cause with CVD and cerebrovascular disease ( 24 ), such non-communicable diseases guide certain comorbidity pathways in the systemic representation of multimorbidity in American adults with perceived cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple risks associated with mental illness which include, but are not limited to, a lack of social connectedness which manifests as isolation or loneliness (Kiely et al , 2021), decreased quality of life (Radicke et al , 2021) and shorter life expectancy than those not suffering from mental illness (Stevenson et al , 2022). Fundamentally, the disadvantage of mental illness is that it not only predisposes individuals to dying by suicide, with almost 90% of those dying from suicide having suffered from a mental illness (Ghossoub et al , 2021), but it also increases their susceptibility to a range of physical health conditions (Launders et al , 2022). The aforementioned dichotomous presentation of wellbeing and mental illness, consequences of experience of mental illness and increased risk of poor mental wellbeing triggered by the COVID-19 pandemic (Campion et al , 2020), suggests the potential benefit in exploring interventions aimed at improving mental wellbeing and strengthening its protective capabilities.…”
Section: Introductionmentioning
confidence: 99%